Off-grid rural electrification using integrated renewable energy sources - Fortune Chukwuebuka Amanze; Destiny Josiah Amanze (Institute of Advanced Engineering and Science, 2021)
Presented in this study is an economic and technical evaluation to determine the optimal system combination for off-grid power generation based on solar, wind, and biodiesel renewable energy resource. Nsukka being endowed with high-intensity solar radiation, adequate wind speed, and sufficient bioresource is a prospective candidate for a hybrid system. The monthly average daily global radiation ranges from 3.91 kWh/m2 to 5.74 kWh/m2 and the average wind speed is about 2.64 m/s. This system was designed to meet the load requirement of the school with annual electrical demand of 10,163 MWh. Sensitivity analysis was carried out based on the effect of changes in biodiesel fuel price and interest rates on the economic performance criteria of the optimal configuration. The optimum hybrid system is composed of a 1 kW capacity PV system, an auto-sized biodiesel generator, and a battery bank of 820 h of autonomy. The levelized cost of energy from the optimal system was found to be 0.0898 per kWh based on sensitivity results. These results obtained show that an integrated system with the combination of PV, biodiesel generator, and battery bank is a cost-effective alternative to grid extension which cost 0.126 per kWh. The system's life span is for 25 years, and it is sustainable, economical, technically feasible, and environmentally friendly.